Enhancing biology laboratory learning: student perceptions of performing heart dissection with virtual reality - Chu, Chui Ee (2024)
In this study, we investigate the attitudes of students towards an immersive educational instruction method used to augment in-person biology laboratories. Specifically, we employ the Oculus Quest 2 in a mid-sized biology classroom setting to conduct a virtual heart dissection instructional class using Virtual Reality (VR). We engaged with 23 students from a Singaporean secondary school to gather insights into their experiences and perspectives. The focus of this study is twofold: firstly, to assess the potential of VR technology, particularly the Oculus Quest 2, as a tool for enhancing learning in biology, and secondly, to evaluate the feasibility of replacing traditional in-person laboratory settings with VR-based learning environments. By examining the students' experiences, this research sheds light on the effectiveness of VR technology in enhancing academic engagement and understanding of this specific content taught in a standardized biology syllabus. Our findings reveal that Oculus Quest 2 with VR can significantly stimulate student interest in this topic. The study provides insights into how VR as part of educational technology can transform the traditional learning experience, offering a more interactive and engaging approach to education in biology. These preliminary results have important implications for the future of educational methodologies in science and technology subjects.